The Safety, Effectiveness, and Efficiency of Autologous Fat Grafting in Breast Surgery. Issue 8 (August 2016) - Spear, Scott L.; Coles, Courtney N.; Leung, Braden K.; Gitlin, Matthew; Parekh, Mousam; Macarios, David
Abstract : Background: For years, the safety and effectiveness of autologous fat grafting (AFG) for breast reconstruction have been in question, with particular concern over fat necrosis, calcifications, cyst formation, and interfering with the detection of breast cancer. However, increasing evidence suggests that the complication rates and clinical results are generally acceptable to both clinicians and patients. The emerging challenge is the numerous AFG techniques and systems, where there are limited knowledge and data. The objective of this study was to conduct a literature review that focuses on the safety, effectiveness, and efficiency of various AFG techniques as applied to the breast. Methods: A PubMed search using terms related to AFG was performed over a 5-year period (April 1, 2010–April 30, 2015). Original articles focused on AFG to the breast, with outcomes on safety, effectiveness, and efficiency, were included. Results: Five hundred ninety-eight articles were identified with 36 articles included (n = 4306 patients). Satisfaction rates were high although the prevalence of complications was low—similar to previous findings. Seven studies reported average operating room time with an overall mean of 125 minutes (range: 40–210). The mean volume of fat harvested was 558 mL (range: 120–1299), and fat injected was 145 mL (range: 20–607). A positive association between injection volume and operating time was observed. Conclusions: This review validates previous findings on the safety and effectiveness of AFG to the breast and highlights its efficiency. The efficiency data available, although limited, suggest that there is an opportunity to achieve time and cost savings while not sacrificing safety and effectiveness.